Pemberdayaan Ekonomi Perempuan, Melalui Sosialisasi Pengolahan Minuman Buah Markisa Sebagai Produk Bisnis Di Desa Bedanten, Kecamatan Bungah Di Kabupaten Gresik - Aulia Rahmi, Vembri; Ernawati, Ernawati (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Passion fruit contains many substances that are useful for the body. Even so, not everyone understands what the health benefits of passion fruit are and are able to process passion fruit into a selling value product. The same thing happened to Bedanten Village, Bungah Sub-Distric, in Gresik Distric with an abundance of passion fruit harvests and the intention was to make preparations made from passion fruit which later hoped to make it the village's superior product developed by the village women's empowerment group. Bedanten Village government officials facilitate the need to create products, through a series of community service activities involving academics to provide direction regarding the processing of passion fruit products. The purpose of service is to increase the knowledge and skills of village women for the welfare of society. The enthusiasm from the community service participants to listen to the socialization of the benefits of passion fruit parts. Participants were so happy and curious when they practiced how to process of making passion fruit. This was followed by exposure to entrepreneurship and digital marketing subjects which motivated them to become interested in entrepreneurial in the village. Therefore, it is necessary to follow up on the results of the service in achieving success in supporting the superiority of village products.